2021
DOI: 10.1016/j.ibneur.2021.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolomic signatures as indicators of injury severity following traumatic brain injury: A pilot study

Abstract: Background Analysis of fluid metabolites has the potential to provide insight into the neuropathophysiology of injury in patients with traumatic brain injury (TBI). Objective Using a 1 H nuclear magnetic resonance (NMR)-based quantitative metabolic profiling approach, this study determined (1) if urinary metabolites change during recovery in patients with mild to severe TBI; (2) whether changes in urinary metabolites correlate to injury severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Previous research from our group revealed potential urinary metabolomics biomarkers for SCI and traumatic brain injury [ 16 , 17 , 18 ]. While more metabolites are detectible in urine through nuclear magnetic resonance (NMR) spectroscopy, it is advantageous to investigate similarities and differences to blood-based biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research from our group revealed potential urinary metabolomics biomarkers for SCI and traumatic brain injury [ 16 , 17 , 18 ]. While more metabolites are detectible in urine through nuclear magnetic resonance (NMR) spectroscopy, it is advantageous to investigate similarities and differences to blood-based biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study demonstrated that there was a positive correlation between urinary 2-hydroxyisobutyrate concentrations and mTBI recovery as well as urinary lactose concentration and number of symptoms 28. Bykowski et al 31 reported a negative correlation between initial GCS taken within 7 days of TBI and three urinary metabolites (homovanillate, L-methionine and thymine) such that these urinary metabolites increased with lower GCS (ie, worse head injury).…”
Section: Resultsmentioning
confidence: 55%
“…However, 82.8% of studies included paediatric subjects. Eight studies specifically examined adult subjects17 22 23 29–33; 41.4% of studies specifically assessed youth, collegiate or professional sport populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 477 In a quantitative profiling study that focused on urinary metabolic signatures including homovanillate, L-methionine, and thymine as indicators of traumatic brain injury. 478 Concerning metabolic signatures of tumor growth stage, such as colorectal cancer, sporadic colorectal adenoma, and the potential metabolites such as D-mannose, sarcosine, 4,5-trimethoxybenzoic acid are found by serum metabolic screening. 479 By metabolic features of PCa analyses, Yu et al discovered a series of altered metabolites that were related to TCA, glycine cleavage system, fatty acid metabolism.…”
Section: Exploring Phenotype Signaturesmentioning
confidence: 99%